Arthroscopic Hip Transcapsular, Translabral Delivery of Orthobiologics for Single-Stage Cartilage Repair - Mario Hevesi, M.D., Ph.D.; Louis Kang, B.S.; Aaron J. Krych, M.D. (Arthroscopy Techniques)
Hip chondral defects often are encountered at the time of hip arthroscopy and can result in substantial pain and dysfunction. With the evolution of cell-based techniques, there is growing interest in single-stage, arthroscopic treatment of such chondral lesions. Arthroscopic orthobiologic delivery remains technically challenging, given the constrained and concave nature of the acetabulum and the need to perform instrumentation taking into account nearby structures such as the articular surface, hip capsule, and labrum. In this Technical Note, we describe our preferred method for arthroscopic delivery of orthobiologics at the time of single-stage cartilage repair, which allows for needle-based transcapsular, translabral access of hip chondral defects for both the acetabulum and femoral head.